Strategy implementation insights from the Competition Commission South Africa - Burke, Mark (My University, 2016)
Knowledge on strategy implementation in the public sector is limited. A deeper understanding of how public sector economic regulators such as competition agencies implement strategies is required to ensure that these organisations are able to reap the benefits of strategy-making and implementation. The purpose of this research was to explore how competition agencies with the mandate to regulate competition implement their strategies by examining the Competition Commission South Africa (CCSA). The research aimed to uncover how the organisation’s processes and practices enable the implementation of its prioritisation strategy and how this contributes to the development of dynamic capabilities. The study identified six organisational processes associated with prioritisation that enable three categories of actions. Firstly, the governance, strategic and business planning, and scoping processes support priority setting in the organisation. Secondly, the resource allocation and case management processes support the marshalling of resources towards assembling the resources required for accomplishing organisational priorities. Thirdly, performance monitoring and evaluation processes are evaluative in that they structure actions that assess progress and account for performance, while making adjustments where required. In the analysis of the four organisational practices associated with prioritisation, it was revealed that each practice constitutes a specific mode of action and promotes specific values. The practice of managing cases from ‘cradle-to-grave’ is an approach that encourages ownership of investigations and cases. The practice of constituting interdivisional teams is a specific form of organisation that promotes joint responsibility and shared accountability. The mid-term review is a mode of alignment as it provides an opportunity to calibrate organisational alignment to priorities in a structured and periodic fashion. The practice of colour-coding the business plan according to organisational priorities is a mode of communication that supports the implementation of priorities. Finally, the research demonstrates how the capabilities built up in the organisation’s priority setting processes, sector expertise, and fledgling project management capacity enable the identification of opportunities and re-configuration of the CCSA resource base to take advantage of those opportunities The study concludes that the implementation of the prioritisation strategy has strengthened the internal capabilities of the CCSA, but that external factors should also be taken into account when evaluating effective regulatory governance.
Graduate School of Governance Master of Management (in the field of Public and Development Management) June 2016
Keywords: Strategic planning--South Africa; Public administration--South Africa